Physiological Effects of Zumba Exercise on Male College Students: An Intervention Study - Prashant Kumar Choudhary; Suchishrava Dubey (OVS LLC, 2024)
Objectives. This study aimed to assess the effectiveness of Zumba exercise in improving physiological parameters among male students enrolled in an aerobic exercise program in Gwalior, Madhya Pradesh, India. Materials and methods. A one-group pre-post-test design was used, involving fifteen male students aged betweennineteen and twenty-four years old. The participants engaged in Zumba sessions supervised by health professionals three times per week for eight weeks. A series of measurements, including VO₂max, agility, and muscle strength, was evaluated at pretest and posttest stages using various equipment and methods. Results. Statistical analysis using SPSS version 26 software included normality testing with the Shapiro-Wilk test and a significance level set at p ≥ 0.05. A paired sample t-test was performed to compare pretest and posttest measurements of VO₂max, agility, and muscle strength. The results are presented as Mean ± Standard Deviation (SD). The findings reveal significant improvements in all parameters assessed post-intervention. VO₂max increased from 26.5 ± 4.5 to 30.8 ± 4.2 mL/kg/min, agility improved from 15.8 ± 1.2 to 14.6 ± 1.3 seconds, limb muscle strength increased from 394.2 ± 66.4 to 411.1 ± 67.5 joules, and arm muscle strength increased from 123.5 ± 17.1 to 138.2 ± 13.9 joules (all p ≤ 0.001). These results demonstrate the effectiveness of Zumba exercise in enhancing physical fitness among male college students. Conclusions. The findings suggest that Zumba exercise is an effective non-pharmacological intervention for enhancing cardiovascular fitness, agility, and muscular strength among male students. Integrating Zumba exercise into regular physical activity routines may contribute to stimulating an active lifestyle and improving overall health outcomes.